Pengaruh Profitabilitas, Leverage, Dan Kualitas Audit Terhadap Kinerja Keuangan Pada Perusahaan Sub Sektor Konstruksi Dan Bangunan Yang Terdaftar Di Bursa Efek Indonesia Periode 2020-2024 - Vania Oriza Satifa; Indrayeni . (CV. ITTC INDONESIA, 2026)
This study aims to analyze the effect of profitability, leverage, and audit quality on financial performance in construction and building sub-sector companies listed on the Indonesia Stock Exchange (2020–2024). Using a quantitative approach, secondary data was gathered from official annual reports. Purposive sampling resulted in 95 observations. Data analysis was conducted using multiple linear regression via SPSS. The results show that profitability (Net Profit Margin) has a positive and significant effect on financial performance (Return on Asset). Leverage (Debt to Equity Ratio) has a negative and significant effect on financial performance. Meanwhile, audit quality has a positive and significant effect on financial performance. These findings suggest that for construction companies, net profit optimization, debt burden control, and the use of credible auditors are essential factors in enhancing the effectiveness of asset utilization and maintaining overall financial stability in a competitive market.